2014
DOI: 10.1016/j.tim.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β and the control of infectious bacterial diseases

Abstract: Glycogen synthesis kinase 3β (GSK3β) has been shown to be a critical mediator of the intensity and direction of the innate immune system responding to bacterial stimuli. This review will focus on: (i) the central role of GSK3β in the regulation of pathogen-induced inflammatory responses through the regulation of pro- and anti-inflammatory cytokine production. (ii) The extensive ongoing efforts to exploit GSK3β for its therapeutic potential in the control of infectious diseases. (iii) The increasing evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
74
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 87 publications
(112 reference statements)
6
74
0
2
Order By: Relevance
“…Treatment with G. procumbens and kaempferol each not only increased survivability of B. pseudomalleiinfected mice but also concomitantly caused inhibition of GSK3β and modulated the pro-and anti-inflammatory cytokine levels. Thus our findings corroborate current understanding that GSK3β is a crucial mediator of the innate immune system response to bacterial infections (Wang et al 2014). In an earlier report (Tay et al 2012), we showed that B. pseudomallei infection-mediated production of pro-inflammatory cytokines (TNF-α, were significantly decreased upon GSK3β inhibition elicited by LiCl treatment.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Treatment with G. procumbens and kaempferol each not only increased survivability of B. pseudomalleiinfected mice but also concomitantly caused inhibition of GSK3β and modulated the pro-and anti-inflammatory cytokine levels. Thus our findings corroborate current understanding that GSK3β is a crucial mediator of the innate immune system response to bacterial infections (Wang et al 2014). In an earlier report (Tay et al 2012), we showed that B. pseudomallei infection-mediated production of pro-inflammatory cytokines (TNF-α, were significantly decreased upon GSK3β inhibition elicited by LiCl treatment.…”
Section: Discussionsupporting
confidence: 91%
“…GSK3 has been established to play important roles in host response to viral, fungal and parasitic infections, including malaria (Wang et al 2014). Inhibition of GSK3β as a consequence of treatment with G. procumbens aqueous extract exhibited chemosuppressive effects, prolonged survivability in P. berghei-infected mice and improved survivability of B. pseudomallei-infected animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ASKa is a member of the evolutionarily conserved GLYCOGEN SYNTHASE KINASE3 (GSK3) class. GSK3 was originally identified as a regulator of glycogen metabolism in mammals but is now recognized as a central multifunctional kinase that acts as a regulator of numerous signaling pathways, including cell fate determination, cell cycle regulation, apoptosis, cancer, and innate immunity in mammals (Jope and Johnson, 2004;Wang et al, 2014). In Arabidopsis, there are 10 GSK3 family members that can be grouped into four classes (Jonak and Hirt, 2002).…”
mentioning
confidence: 99%